2007
DOI: 10.1371/journal.pone.0000430
|View full text |Cite
|
Sign up to set email alerts
|

ATM-Mediated Transcriptional and Developmental Responses to γ-rays in Arabidopsis

Abstract: ATM (Ataxia Telangiectasia Mutated) is an essential checkpoint kinase that signals DNA double-strand breaks in eukaryotes. Its depletion causes meiotic and somatic defects in Arabidopsis and progressive motor impairment accompanied by several cell deficiencies in patients with ataxia telangiectasia (AT). To obtain a comprehensive view of the ATM pathway in plants, we performed a time-course analysis of seedling responses by combining confocal laser scanning microscopy studies of root development and genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
111
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 197 publications
(281 reference statements)
10
111
0
Order By: Relevance
“…The transcriptional induction of ERF115 has not been previously observed in IR-response transcriptomes (Ricaud et al, 2007;Yoshiyama et al, 2009;Missirian et al, 2014), possibly due to its localized expression in a small subset of cells. Nonetheless, this discrepancy did raise the question of whether its IR induction is an artifact of the GUS or GFP fusion transgenes, rather than the native gene.…”
Section: Sog1 Is Required For Cell Cycle Arrest Immediately After Irmentioning
confidence: 82%
See 1 more Smart Citation
“…The transcriptional induction of ERF115 has not been previously observed in IR-response transcriptomes (Ricaud et al, 2007;Yoshiyama et al, 2009;Missirian et al, 2014), possibly due to its localized expression in a small subset of cells. Nonetheless, this discrepancy did raise the question of whether its IR induction is an artifact of the GUS or GFP fusion transgenes, rather than the native gene.…”
Section: Sog1 Is Required For Cell Cycle Arrest Immediately After Irmentioning
confidence: 82%
“…ATM (Yoshiyama et al, 2013) and inferably ATR (Furukawa et al, 2010;Yoshiyama et al, 2009) can phosphoactivate the transcription factor SOG1, as well as other proteins, in plant cells (Roitinger et al, 2015;Yoshiyama et al, 2013). Once activated, SOG1 transcriptionally induces various functional classes of DDR genes (Yoshiyama et al, 2009;Missirian et al, 2014;Ricaud et al, 2007); SOG1 induces a robust set of .100 transcripts by $4-fold within 1.5 h in response to 100 Gy IR (Culligan et al, 2006;Furukawa et al, 2010). SOG1 has a known role in transcriptionally inhibiting cell cycle progression in response to DNA damage (Preuss and Britt, 2003;Yoshiyama et al, 2009).…”
mentioning
confidence: 99%
“…S3). Higher doses of zeocin caused permanent arrest of the root meristem and death of the QC and provascular cells, which has been interpreted as a consequence of premature differentiation (18) (Fig. S1).…”
Section: Rootmentioning
confidence: 99%
“…However, accumulation of GFP fused to the destruction box of CYCB1;1 (CYCB1;1-GFP), which marks cells that are likely to be arrested in G2 phase (17,18,27), showed that the response to zeocin was widespread in the root tip ( Fig. 1D; an untreated CYCB1;1-GFP control is shown in Fig.…”
Section: Rootmentioning
confidence: 99%
See 1 more Smart Citation